DEVELOPMENT OF CHARACTER-BASED VIDEO LEARNING MEDIA TO ENHANCE ANECDOTE TEXT WRITING SKILLS AMONG MA STUDENTS - Zahara, Luhlu; Kusumawati, Tri Indah (Universitas Muhammadiyah Makassar, 2025)
This study was motivated by the low ability of students at MA Muhammadiyah 01 Medan to write anecdotal texts, which requires innovative learning media to make the learning process more engaging and effective. The primary objective of this research was to develop a character video learning media that is valid, practical, and effective in improving the anecdotal text writing skills of tenth-grade students. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects consisted of tenth-grade students and experts who validated the content, media, and language aspects. Data collection techniques included observation, expert validation questionnaires, practicality questionnaires for teachers and students, and post-tests to measure students’ learning outcomes. Expert validation results indicated that the character video media is highly feasible for use, with high validity scores. Practicality tests from teacher questionnaires scored 97%, student questionnaires scored 89%, and learning implementation scored 91, all categorized as very good, indicating that the media is highly suitable and easy to apply in the learning process. Moreover, post-test results showed a significant improvement in students’ ability to write anecdotal texts after using the character video media. These findings confirm that the use of character video media provides a more interactive and contextual learning experience compared to conventional methods such as lectures. This study contributes significantly to the development of digital learning media, particularly for Indonesian language subjects, and can serve as a reference for educators in creating learning materials that align with students’ needs and interests.